Effects of energy level and lasalocid on productivity of fall-calving,first-calf heifers - Goehring, T.; Corah, L.; Higgins, James J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Fall-calving, first-calf heifers (136 head) were fed TDN levels approximating 85% or 100% of NRC recommendations, with or without 200 mg/hd/day lasalocid. Those fed the recommended diet gained more weight from 130 days prepartum to calving and showed more improvement in condition score before calving than those on the low-energy diet. After calving, the group fed the recommended energy level lost less weight and condition and had better reproductive performance than the low-energy group. The only effect of lasalocid was to improve calf performance in the low-energy group.
Keywords: Beef; Energy; Lasalocid; Heifers